Effect of calcium carbonate on solid fermentation of Solanum tuberosum post-harvest wastes, inoculated with a microbial preparation - Borrás, L. M.; Valiño, Elaine; Elías, A.; Martínez, J. J.; Sanabria, A. M.; Becerra, Mónica (Cuban Journal of Agricultural Science, 2020)
To evaluate the effect of including calcium carbonate (CaCO3) in solid fermentation of post-harvest wastes of Solanum tuberosum (potato), inoculated with a microbial preparation, a completely randomized design was used, with three repetitions per treatment. Indicators pH, dry matter, crude protein, true protein and concentration of microorganisms were analyzed according to a 2x2x4 factorial arrangement, in which factors were fermentation time (24 and 48 h), incubation temperature (20 and 25 ºC) and percentage of inclusion of CaCO3 (0, 0.25, 0.50 and 0.75 %). For the concentration of organic acids and ammonia, a 2x2x3 factorial arrangement was used, which differed from the previous one in the percentage of CaCO3 (0.25, 0.50 and 0.75 %). It was obtained that pH increased by adding CaCO3 at 0.25 and 0.50 % and incubating at 20 or 25 ºC. Meanwhile, pH decreased with fermentation and incubation at 20ºC. Lactic acid production increased with both temperatures and during fermentation, and growth of mesophilic and lactic aerobic bacteria was favored with the inclusion of CaCO3. With fermentation, dry matter and crude and true protein percentages increased. The highest values of these indicators were obtained with 0.50% of CaCO3 at 48 h (40.90, 19.09 and 13.8 %, respectively). However, protein synthesis was the same at 20 °C and 25 °C (72.76 %). It is concluded that CaCO3 at 0.50% favors the fermentation of post-harvest wastes of S. tuberosum with the microbial preparation, at 20 °C and 24 h. Keywords: potato, silage, lactobacilli, additive